PEMBINAAN KEPARIWISATAAN MELALUI PELATIHAN ETIKA PELAYANAN PEKERJA WANITA DI ART SHOP DESA ADAT SEMINYAK KABUPATEN BADUNG - Putu Diah Kesumadewi; Ni Made Ariani; A.A Manik Pratiwi; Putu Sucita Yanthy (Buletin Udayana Mengabdi, 2018)
The tourism industry is very fast growing nowadays in Desa Adat Seminyak. One of the tourism industries that supports the existence of tourism in Desa Adat Seminyak is the art shop. The existence of art shop invites tourists who visit the area of Seminyak and surrounding areas to shop for various needs at the venue. Usually goods purchased by tourists to be brought as a fruit hand to place of origin. Not infrequently tourists also shop at the art shop for business purposes, because the goods purchased can also be resold in the area of origin. The Art shop in Desa Adat Seminyak is expected to benefit the local community in this village. Therefore most workers are expected to come from the village. Most art shop workers in Desa Adat Seminyak are female workers. This is because working in the art shop does not require heavy power and can set the time because it is not bound by the work time. Female workers are considered very suitable to work in the art shop because it has good selling ability. But not just the ability to sell that must be owned by female workers, another ability that must be owned by female workers is the ability to serve consumers in this case tourists. Good service is needed by female workers so that tourists can comfortably shop at the art shop in Desa Adat Seminyak. One way that can be done to implement good service by female art shop workers is by providing training of service ethics to these workers. The service ethics training model that can be applied to female workers in art shop is in various ways, such as the ethics of foreign-language communication, good-looking ethics and good conduct ethics. Through this devotion is expected to form a good service ethics to female art shop workers so that the quality of service can be good. Good service quality is expected to be able to make a positive impact for the existence of tourism in Desa Adat Seminyak.